2014
DOI: 10.1007/s00300-014-1598-3
|View full text |Cite
|
Sign up to set email alerts
|

Diverse metabolic and stress-tolerance pathways in chasmoendolithic and soil communities of Miers Valley, McMurdo Dry Valleys, Antarctica

Abstract: The majority of biomass in the McMurdo Dry Valleys of Antarctica occurs within rocks and soils, but despite the wealth of biodiversity data very little is known about the potential functionality of communities within these substrates. The putative physiological capacity of microbial communities in granite boulders (chasmoendoliths) and soils of a maritime-influenced Antarctic Dry Valleys were interrogated using the GeoChip microarray. Diversity estimates revealed surprisingly high diversity and evenness in bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
1
8
2
1
Order By: Relevance
“…Our data showed that, among the studied microeukaryotic groups, the fungal phyla Ascomycota and Basidiomycota dominated the study area likely due to the highly diverse ecological functions they can play: decomposers, parasites, or mutualists (Yergeau et al, 2007;Honegger, 2012;Tedersoo et al, 2014;Wei et al, 2015). The unraveled taxonomic diversity is in accordance with previous studies that used culturedependent and high-throughput sequencing data to explore several Antarctic habitats (Bridge and Newsham, 2009;Arenz et al, 2014;Baeza et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…Our data showed that, among the studied microeukaryotic groups, the fungal phyla Ascomycota and Basidiomycota dominated the study area likely due to the highly diverse ecological functions they can play: decomposers, parasites, or mutualists (Yergeau et al, 2007;Honegger, 2012;Tedersoo et al, 2014;Wei et al, 2015). The unraveled taxonomic diversity is in accordance with previous studies that used culturedependent and high-throughput sequencing data to explore several Antarctic habitats (Bridge and Newsham, 2009;Arenz et al, 2014;Baeza et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…We did not find any archaeal sequences in our endolith metagenomes, which is consistent with low abundance or absence of archaea in previous studies of lithobiontic habitats (Wood et al, 2008;Pointing et al, 2009;Wong et al, 2010;Stomeo et al, 2012;DiRuggiero et al, 2013;Vikram et al, 2015) In term of biogeochemical cycling genes, the identification of photosynthesis and carbon fixation pathways from the metagenomes confirmed that primary production was mainly carried out via photosynthesis. However, in contrast to Antarctic cryptoendolithic communities, we did not detect any genes for chemolithoautotrophy (Wei et al, 2015). Genes for diazotrophy were also absent from both metagenomes and the major sources of nitrogen for the communities were potentially ammonia and nitrates.…”
Section: Discussioncontrasting
confidence: 80%
“…Habitats as different as the underside of quartz rocks (Azúa-Bustos et al, 2011;Cowan et al, 2011;Chan et al, 2013;de los Ríos et al, 2014;Vikram et al, 2015), sandstones (Friedmann, 1982;de la Torre et al, 2003;Pointing et al, 2009), granite boulders (Wei et al, 2015), the inside of gypsum (Dong et al, 2007;Wierzchos et al, 2011Wierzchos et al, , 2015 and halite evaporites (Wierzchos et al, 2006;Robinson et al, 2015), carbonaceous (DiRuggiero et al, 2013) and volcanic rocks Cámara et al, 2014) among others, have shown that life has found innovative ways to adapt to the extreme conditions of hyper-arid deserts.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the important role of microorganisms as early colonizers in primary succession, most of the studies examining community change during primary succession have historically focused on plant communities [4]. However, primary succession can also occur in microbial habitats, including the surfaces of plant leaves and flowers [5][6][7], exposed rock surfaces [8], glacial sediments [9][10][11], animal guts [12], and biofilms [13]. Furthermore, studying primary succession from a microbial perspective has the added advantage that ecologists can examine community development patterns in a time frame far shorter than what would be required to track primary succession patterns in plant or animal communities [14].…”
Section: Introductionmentioning
confidence: 99%